Ultrasound- and hemicellulase-assisted extraction increase β-glucosidase activity, the content of isoflavone aglycones and antioxidant potential of soymilk - Mariah Benine Ramos Silva; Heloisa Gabriel Falcão; Louise Emy Kurozawa; Sandra Helena Prudencio; Adriano Costa de Camargo; Fereidoon Shahidi; Elza Iouko Ida (Journal of Food Bioactives, 2019)
Soymilk is consumed as such or used in the preparation of tofu, fermented soymilk, and soy yogurt, among others. In this study, hemicellulase-assisted extraction (HAE) and ultrasound-assisted extraction (UAE) were used during soymilk manufacturing. The activity of endogenous β-glicosidases was increased 1.3 and 1.5-fold in soymilk produced upon HAE and UAE, respectively. Likewise, the concentration of isoflavones in the aglycone form increased 1.7 and 2.4 times in samples subjected to HAE and UAE, respectively. UAE, but not HAE, rendered an equimolar conversion from conjugated isoflavones to their respective aglycones. In addition, HAE and UAE showed higher antiradical activity towards ABTS radical cation and peroxyl radical, compared to those of the control. The aglycone isoflavones/conjugated isoflavones (aISO/cISO) ratio correlated with the antiradical activity, thus suggesting that the soybean industry may use this new quality index to indicate the antioxidant potential of products. Food formulations containing soymilk with high aISO/cISO ratio may translate to higher oxidative stability of the final product. Likewise, the higher absorption of aglycone isoflavones compared to that of their conjugated counterparts is well recognized. Therefore, high aISO/cISO ratio of soymilk and/or its products may provide a better antioxidant protection under physiological conditions.